ArfA recognizes the lack of mRNA in the mRNA channel after RF2 binding for ribosome rescue - Kurita, Daisuke (Nucleic Acids Res, 2014)
Although trans-translation mediated by tmRNA-SmpB has long been known as the sole system to relieve bacterial stalled ribosomes, ArfA has recently been identified as an alternative factor for ribosome rescue in Escherichia coli. This process requires hydrolysis of nascent peptidyl-tRNA by RF2, which usually acts as a stop codon-specific peptide release factor. It poses a fascinating question of how ArfA and RF2 recognize and rescue the stalled ribosome. Here, we mapped the location of ArfA in the stalled ribosome by directed hydroxyl radical probing. It revealed an ArfA-binding site around the neck region of the 30S subunit in which the N- and C-terminal regions of ArfA are close to the decoding center and the mRNA entry channel, respectively. ArfA and RF2 sequentially enter the ribosome stalled in either the middle or 3′ end of mRNA, whereas RF2 induces a productive conformational change of ArfA only when ribosome is stalled at the 3′ end of mRNA. On the basis of these results, we propose that ArfA functions as the sensor to recognize the target ribosome after RF2 binding.